Epigenetically Modified Endothelial Progenitor Cells in Heart Failure - Berezin, A. E.; Березін, Олександр Євгенійович (iMedPub, 2016)
Heart failure is a global health and medical problem that increases burden of cardiovascular (CV) disease. By now, there is not completely recognition regarding the reasons of various phenotypes of HF development, distinguish in CV risk, clinical outcomes and prognosis. It has suggested epigenetic modification of several cell components of endogenous repair system might determine phenotypical response of the failing heart and contributes to nature evolution of HF. Moreover, epigenetically modified endothelial progenitor cells playing a central role in the tissue reparation and angiogenesis may link aging, genetic predisposition, co-morbidities, traditional CV risk factor and HF progression. The editorial comment devotes the Consideration of the role of epigenetic in manifestation of progenitor endothelial cell dysfunction and perspectives to restore its reparative ability in HF individuals.
Keywords: Heart failure; Progenitor cells; Endothelial dysfunction; Epigenetics; Prediction